A Cu(ii)-triggered release system by l-cysteine functionalized gold nanoparticles for "on-demand" molecular delivery and bioimaging in cells. Issue 10 (7th August 2021) - Li, Shaoqing; Huang, Wei; Tan, Wei; Zhang, Lizhu; Zhang, Yanli; Shi, Hongyu; Mathesh, Motilal; Barrow, Colin J.; Yang, Wenrong; Wang, Hongbin
Abstract : Schematic description of GNP–l -Cys–Rh6G2 with Cu(ii ) triggered release. Abstract : Functionalized gold nanoparticles (GNPs) have been extensively studied for cargo delivery and imaging towards biomedical applications. However, there are limited studies showcasing the above two in sync using GNPs. In this work, we fabricated a nanosystem for small molecule delivery and bioimaging based on l -cysteine (l -Cys)-functionalized GNPs (GNP–l -Cys) coupled with a rhodamine 6G derivative (Rh6G2). GNPs conjugated with Rh6G2 (GNP–l -Cys–Rh6G2), as a model system, showcased enhanced fluorescence emission due to "on-demand" release of the rhodamine dye (RGCOOH) from the surface of the GNPs through spiro ring-opening followed by an ion-catalyzed hydrolysis mechanism in the presence of Cu 2+ . Moreover, in vitro studies showed sustained release of RGCOOH into cells; thus, GNP–l -Cys–Rh6G2 acted as a delivery vehicle without causing significant cell toxicity and was further used for fluorescence imaging. We believe such nanoscale systems with molecular scale engineering open up new possibilities for biomedical applications.